Eosinophilic esophagitis strongly linked to chronic rhinosinusitis. (26th November 2015) - Padia, Reema; Curtin, Karen; Peterson, Kathryn; Orlandi, Richard R.; Alt, Jeremiah
Abstract : Objectives/Hypothesis: To determine the relative risk of having eosinophilic esophagitis (EoE) coexist with chronic rhinosinusitis (CRS) in probands and their families using the Utah Population Database (UPDB). Methods: This retrospective observational cohort study with population‐based matched controls utilized the UPDB, a genealogical database linked to medical records. It was used to identify CRS and EoE patients diagnosed at any age between 2008 and 2012. The familial risks of an EoE diagnosis (International Classification of Diseases, Ninth Revision, Clinical Modification code 530.13) in CRS probands, and vice versa, and their first‐ through fifth‐degree relatives and spouses were calculated using logistic regression models in comparison to controls randomly selected from the Utah population and individually matched 6:1 on sex and birth year. Results: Probands with CRS demonstrated a 3.4‐fold increased risk of having EoE themselves ( P < 10 −15 ). First‐degree relatives (parents, siblings, and children) of CRS probands had a 1.5‐fold increased risk of having EoE ( P < 10 −4 ), whereas more distant relatives did not show a significant increased risk. Spouses of probands had a 1.4‐fold increased risk of having EoE ( P = 0.055). Conversely, risk estimates of having CRS in EoE probands were consistent. Conclusion: We observed an increased risk of comorbid EoE in patients with CRS and their families. An association between CRS and EoE as comorbid conditions suggests that a familial component is contributing to the etiology of both diseases. Further analyses regarding the pathophysiology of the development of CRS in these specific patients will lead to a better understanding of both disease processes and may help target therapy. Level of Evidence: 3b. Laryngoscope, 126:1279–1283, 2016